Rare Case of Multiple Lineage Dysplasia Myelodysplastic Syndrome Presenting with Only Anemia: A Case Report - Sutandyo, Noorwati; Rinaldi, Ikhwan; Mulya Sari, Resti; Susanto Kosasih, Agus; Setiawan, Lyana; Winston, Kevin (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Myelodysplastic syndrome (MDS) is a heterogeneous group of hematopoietic stem cell disorders which is characterized by ineffective hematopoiesis and risk of progression into acute myeloid leukemia. The diagnosis and classification of MDS are determined from the findings of dysplasia in one or more cell lineage and the percentage of blast cell on bone marrow examination. However, it should be noted that an abnormality in one marrow cell lineage does not necessarily translate to the corresponding clinical phenotype. Here, we present a case of MDS with multilineage dysplasia (MLD) (erythrocyte, leukocyte, and thrombocyte) from bone marrow aspiration, but with anemia as the sole clinical manifestation (single cytopenia). CASE REPORT: A 78-year-old male patient came to our clinic on July 10, 2020, with chief complaint of worsening fatigue which started approximately 1 year before visit. His vital signs during the visit were stable and no other abnormalities observed other than pale conjunctivae. Complete blood count showed macrocytic anemia with no abnormalities in leukocyte count and thrombocyte count, which suggested a single cytopenia. Peripheral blood smear was negative for megaloblasts and hypersegmented neutrophils. The patient’s bone marrow examination showed MDS with MLD. This result was in contrast to complete blood count examination which only showed anemia (single cytopenia). CONCLUSION: This case showed that there could be discrepancy between clinical manifestations of the cytopenia with bone marrow dysplasia, which highlighted the importance of conducting bone marrow examination to properly classify MDS type.